2019
DOI: 10.1109/access.2019.2944948
|View full text |Cite
|
Sign up to set email alerts
|

Secure Energy-Efficient Transmission for SWIPT Intelligent Connected Vehicles With Imperfect CSI

Abstract: In this paper, the secure energy-efficient transmission problem for an artificial-noise (AN)aided simultaneous wireless information and power transfer (SWIPT) and vehicle-to-infrastructure (V2I) communication system with the imperfect channel state information (CSI) is studied. The secure energy efficiency problem is formulated with the imperfect CSI, where the constraints contain the minimum secrecy rate request of the legitimate vehicle (LV), the minimum energy harvesting (EH) request, the maximum transmit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…the research on PLS with imperfect CSI plays a significant role for the future deployment of PLS in 5G networks [31]. We combed some recent papers on imperfect CSI in PLS [32]- [34]. These papers revealed that the imperfect CSI will reduce the secrecy performance of the considered networks, and can provide guidance for related research under imperfect CSI.…”
Section: A Backgroundmentioning
confidence: 99%
“…the research on PLS with imperfect CSI plays a significant role for the future deployment of PLS in 5G networks [31]. We combed some recent papers on imperfect CSI in PLS [32]- [34]. These papers revealed that the imperfect CSI will reduce the secrecy performance of the considered networks, and can provide guidance for related research under imperfect CSI.…”
Section: A Backgroundmentioning
confidence: 99%
“…Where cd   is the path loss, d means the distance between the user and the base station,  is the path loss index, and c is the transmission constant. s represents log-normal shadow distribution, and W represents small-scale fading [11]. Due to the existence of channel estimation errors, it is difficult to achieve perfect channel information estimation in practical applications.…”
Section: System Model and Problem Formationmentioning
confidence: 99%
“…According to the maximum ratio transmission strategy, the zero-forcing precoding matrix is expressed as [11]:…”
Section: System Model and Problem Formationmentioning
confidence: 99%
“…Note that most of the papers focused on supporting low latency and high reliable services. For example, the authors in [35] considered the secure energy-efficient transmission in the context of SWIPT and vehicle-to-infrastructure (V2I) communication system with the imperfect channel state information (CSI). However, they did not apply the advantage of CR and NOMA.…”
Section: Our Contributionmentioning
confidence: 99%